Advancing Regenerative Farming Based on Community Services and Research-Based Experiences Through Building a Sense of Cultural Identity and Pride Among Farmers and Their Children at Subak Uma Lambing - Bustamante, Jan Henrick Gonzales; Guerina, Roy Salvamante; Recto, Imee Bello; Tomas, Ricky San Lorenzo Sto.; Tirao, Gladys Hope Aracan; Sumayo, Romeo M.; Santhi, Ni Nyoman Putri Purnama; Astiti, Ni Made Ayu Gemuh Rasa; Sukmadewi, Desak Ketut Tristiana; Mangku, I Gede Pasek; Situmeang, Yohanes Parlindungan; Astara, I Wayan Wesna; Ciandani, Ni Luh Vigrah Purnama; Prakerti, Ni Luh Adelia Darma (Asia Pacific Network for Sustainable Agriculture, Food and Energy (SAFE-Network), 2025)
This study examines how the community at Subak Uma Lambing in Bali, Indonesia, can advance regenerative farming initiatives by strengthening farmers' and their children's cultural identity and pride. Through community engagement and research-based approaches, this study explores the behavioral factors that influence the adoption of regenerative agricultural practices. By deepening the community’s connection to its cultural heritage, this research seeks to enhance motivation toward sustainable farming and ensure the preservation of local traditions for future generations. The revitalization of agriculture in Subak Uma Lambing relies on cultivating a strong sense of cultural identity, particularly among the younger generation. Strengthening this cultural bond is essential for fostering a resilient agricultural system that honors tradition while integrating innovation. By instilling an appreciation for farming from an early age, this study aims to promote long-term sustainability and prosperity for the Subak Uma Lambing community.Contribution to Sustainable Development Goals (SDGs)SDG 2 (Zero Hunger)SDG 4 (Quality Education)SDG 11 (Sustainable Cities and Communities)SDG 12 (Responsible Consumption and Production):SDG 15 (Life on Land)